O autoconceito dos agressores de violência doméstica contra a mulher em Santa Maria, Rio Grande do Sul - Roso, Patricia Lucion (2019)
This research aims to investigate, through psychological evaluation, domestic violence perpetrators against women. To determine if there is an association between sociodemographic profile, attachment types and social desirability, the study uses the Marlowe-Crowne Social Desirability Scale (MC-SDS) as technical instruments; the Next Relationship Scale (ECR-RS); and a Sociodemographic Record. The increasing rates of violence against women in Brazil and in the world, is it important to see the necessity for studies that address this issue. There are a huge literature with data about the victim, however, sparing is the production about the aggressor. In this way, the research aims to contribute with the scientific community and civil society, at the moment that looks at domestic violence with a focus on the aggressor, in an attempt to offer reflections about self-concept, manipulation, attachment and sociodemographic characteristics the executioner's behavior. Thirty female aggressors with a record of occurrence of violence against women in Santa Maria, Rio Grande do Sul were evaluated. The results were treated with descriptive statistical techniques (to analyze sociodemographic data) and inferential, using the chi-square test (to evaluate associations between the types of attachment). Concerning the sociodemographic profile, most of the aggressors have little schooling, are between 30 and 40 years old, are single and have practiced physical and psychological violence, and the reasons for violence are varied. It was verified that the subjects of research tend to present a manipulative behavior, there is a tendency to present with distortion of the self-concept in order to be socially accepted. They are prone to the establish fragile relational bonds of love, with the type insecure attachment worried, which comes from the representational models they had with the maternal and paternal figures.